Réponses

2013-07-08T10:20:51+02:00

a) déjà factorisé

 

b)

f(x) = x²-4(x-5)² 
f(x) = x² - [ 2(x-5) ]² 
f(x) = [x - (2x-10)] ( x +2x-10) 
f(x)=(x-2x+10)(x+2x-10)
f(x) = (-x+10)(3x-10)

 

c)

f(x)=2(x-3)(x+7)-(2x+1)(x+7)

f(x)=(2x-6)(x+7)-(2x+1)(x+7)

f(x)=(x+7)(2x-6-2x-1)

f(x)=-7(x+7)

 

d)déjà factorisé

 

e)

f(x)=(x-2)(x+1)-(x²-4)

f(x)=(x-2)(x+1)-(x²-2²)

f(x)=(x-2)(x+1)-(x-2)(x+2)

f(x)=(x-2)(x+1-(x+2)

f(x)=(x-2)(x+1-x-2)

f(x)=(x-2)(-1)

f(x)=-x+2

 

f)

f(x)=x²-12x+36

(a-b)²=a²-2ab+b²

f(x)=(x-6)²

 

g)

f(x)=x(3x-5)-(3x-5)

f(x)=(3x-5)(x-1)

 

h)

f(x)=x²-1-3x(x+1)

f(x)=(x-1)(x+1)-3x(x+1)

f(x)=(x+1)(x-1-3x)

f(x)=(x+1)(-2x-1)